Widespread Shrubification on European Mountain Summits - Thomas Vanneste; Harald Pauli; Stefan Dullinger; Bente J. Graae; Otar Abdaladze; José Luis Benito Alonso; Christopher Andrews; Peter Barančok; Manfred Bardy‐Durchhalter; Haben Blondeel; Pau Carnicero; Emmanuel Corcket; et al. (Global Change Biology, 2026)
Shrubs are expanding across the cold ecosystems of our planet with potentially profound consequences for their biodiversity and functioning. However, evidence is still strongly biased towards the Arctic tundra, while a large‐scale assessment of shrub expansion in alpine areas above the elevational treeline is missing so far. Here we quantified shrub cover changes over the past two decades in 576 permanent plots of 1 m 2 spread across the alpine vegetation belt of Europe's major mountain chains. Total shrub cover clearly increased in the plots with an average rate of about 2.6% per m 2 per decade (95% CI = 1.9%–3.4%), and this expansion was more pronounced for evergreen (2.0% per m 2 per decade, CI = 1.3%–2.7%) than for deciduous species (1.7% per m 2 per decade, CI = 0.9%–2.4%). The magnitude of individual species' cover shifts was positively associated with their plant height, but negatively with their leaf nitrogen content and light affinity. In sum, we show that shrub expansion is a widespread phenomenon also in the alpine zone of European mountains, with potentially far‐reaching consequences for alpine plant dynamics, soil microclimates, snow patterns, carbon cycling, food chains and livelihoods.